Nephropathy Symptoms in Type-2 Diabetic Patients and Their Relationship with Daily Exerciser and Sunlight Exposure - Alam, Md Minhazul; Chowdhury, Sumon Rahman; Islam, S K M Azizul (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Type 2 Diabetes Mellitus (T2 DM) is chronic metabolic disorder withan increasing prevalence worldwide and manifolds with high morbidity and mortality in both developed and developing countries. It can cause complications if remain uncontrolled. The aim of the study was to find out the socioeconomic status, complications associated with diabetic neuropathy and correlation with life style. Materials and methods: A cross sectional study was carried out for a period of one year (October 2020 to October 2021) among the diagnosed T2 DM patients in Southern Medical College Hospital (SMCH) Chattogram, Diabetic General Hospital (CDGH) and author’s personal chamber. Total 158 patients were enrolled for this study and data were collected through a pre-structured questionnaire.Collected data were entered into the MS Excel-2010, sorted out and exported to Statistical Package for Social Sciences (SPSS) Version 20.0. Descriptive statistics were performed followed by student’s t-test, Chisquare test among different groups then correlation and multiple linear regression analysis were performed. Results: Among total enrolled patients, 72(46%) were male and 86(54%) were female where 62% patents lived in urban areas. 13.3% of the patients didn’t perform any daily exercise and 27% led a sedentary life style. 61.4% had daily sunlight exposure varying from few hours to 6-8 hours where 58(80.6%) were male and 39(45.3%) were female (p<0.00) respectively. Chi-square test showed increase prevalence for HTN and Dyslipidaemia (p<0.05) regarding daily exercise. Increased prevalence of periodontitis, Feet/Leg cramps, GIT problems infemale sex were predominant as opposed to males due to less daily sunlight exposure. Multiple linear regressions confirmed that sex (p=.000) plays an important roleregarding diabetic neuropathy related symptoms and complications, where female had morediabetic neuropathy related symptoms and complications than males (b=.341, 95% CI=.190 .477, p =0.000) with less daily sunlight exposure. Conclusion: Female has less sunlight exposure than male, so they likely have less vitamin D level than male which might triggers diabetic neuropathy symptoms. So every T2 DM patient should routinely assay vitamin D level. JCMCTA 2023 ; 34 (1) : 57-63